Enhancing the Obsolescing Bargain Theory: A Longitudinal Study of Foreign Ownership of U.S. and European Multinationals - Vachani, Sushil (Journal of International Business Studies, 1995)
This research attempts to enhance the obsolescing bargain theory, for manufacturing companies, by statistically testing the effects of nine explanatory variables on the static and dynamic manifestations of bargaining success, with longitudinal, firm-level data. In order to highlight those effects, it develops a conceptual framework that provides a broader context in which the primary variables operate. It demonstrates that the obsolescing bargain took effect in India over a fifteen-year period following restrictive legislation. Unlike previous research, this study measures the effect of benefits received by multinationals from the host government in exchange for equity dilution. American companies are found to retain a smaller share of their foreign ownership over time than British and other European multinationals. Some explanatory variables that have previously been found to influence level of foreign ownership (static bargaining success) are found to be less important, or have a different effect, in explaining proportion of foreign ownership retained (dynamic bargaining success).